Perbandingan Nilai Cadangan Premi Tahunan Asuransi Jiwa Menggunakan Metode Fackler Berdasarkan Tingkat Suku Bunga - Putri, Nadila; Muchlian, Melvi; yurniati, Yurniati (Program Studi Aktuaria, Fakultas Sains Teknologi dan Pendidikan, Universitas Tamansiswa Padang, 2023)
Abstract This study discusses the calculation and comparison of the value of the annual premium reserve for life insurance using the Fackler method based on interest rates, namely 3.50% and 3.75%. In calculating the premium reserve value required is the insurance coverage value, the annual premium value (??) is based on the commutation table from the 2011 mortality table which is influenced by interest rate factors. Based on the results of calculations and discussions, it can be concluded that the final reserve value for life insurance premiums using the Fackler method based on an interest rate of 3.50% is greater than that of an interest rate of 3.75%. Premium reserves obtainedusing the fackler method increase from the first year reserves to year-end reserves based on the sum insured, it can be concluded that the premium reserve value is greaterusing a small interest rate compared to a larger interest rate.